2021
DOI: 10.1371/journal.pone.0259241
|View full text |Cite
|
Sign up to set email alerts
|

The glutaminase inhibitor telaglenastat enhances the antitumor activity of signal transduction inhibitors everolimus and cabozantinib in models of renal cell carcinoma

Abstract: Dysregulated metabolism is a hallmark of cancer that manifests through alterations in bioenergetic and biosynthetic pathways to enable tumor cell proliferation and survival. Tumor cells exhibit high rates of glycolysis, a phenomenon known as the Warburg effect, and an increase in glutamine consumption to support the tricarboxylic acid (TCA) cycle. Renal cell carcinoma (RCC) tumors express high levels of glutaminase (GLS), the enzyme required for the first step in metabolic conversion of glutamine to glutamate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…The drop of glutamate and glutamine observed in VHL- ccRCC cells in response to STF-62247 was particularly interesting since these tumors rely on glutamine for growth and proliferation. In fact, glutaminase inhibitors showed anti-proliferative activity in vitro and in vivo in mice in a wide range of cancer models including RCC ( 33 , 58 , 59 ). However, clinical trials using GLS inhibitor Telaglenastat (CB-839) combined with the mTOR inhibitor everolimus showed a modest improvement of progression-free survival (PFS) from 1.9 months to 3.8 months while it fails to increase PFS in advanced ccRCC in combination with cabozantinib ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The drop of glutamate and glutamine observed in VHL- ccRCC cells in response to STF-62247 was particularly interesting since these tumors rely on glutamine for growth and proliferation. In fact, glutaminase inhibitors showed anti-proliferative activity in vitro and in vivo in mice in a wide range of cancer models including RCC ( 33 , 58 , 59 ). However, clinical trials using GLS inhibitor Telaglenastat (CB-839) combined with the mTOR inhibitor everolimus showed a modest improvement of progression-free survival (PFS) from 1.9 months to 3.8 months while it fails to increase PFS in advanced ccRCC in combination with cabozantinib ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, glutaminase inhibitors showed anti-proliferative activity in vitro and in vivo in mice in a wide range of cancer models including RCC ( 33 , 58 , 59 ). However, clinical trials using GLS inhibitor Telaglenastat (CB-839) combined with the mTOR inhibitor everolimus showed a modest improvement of progression-free survival (PFS) from 1.9 months to 3.8 months while it fails to increase PFS in advanced ccRCC in combination with cabozantinib ( 33 ). Our study demonstrated that STF-62247 significantly decreased intracellular levels of glutamine and glutamate without affecting GLS activity, ATP levels, mitochondrial oxygen consumption or mitochondrial membrane potential (data not shown) in VHL- cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cabozantinib inhibits the growth factor receptors VEGFR, MET and AXL and has downstream effects on the PI3K/AKT/mTOR pathway, leading to a decreased glucose utilization. In a preclinical model, the dual inhibition of glutamine and glucose metabolism showed enhanced anti-tumor activity [ 54 ].…”
Section: Novel Targetsmentioning
confidence: 99%
“…This increase in glutamine metabolism fuels tumor cell proliferation and survival and is dependent on the catalytic activity of the enzyme glutaminase . Renal cell carcinoma cell lines have been shown to overexpress glutaminase …”
Section: Introductionmentioning
confidence: 97%